2012
DOI: 10.1113/jphysiol.2011.224717
|View full text |Cite
|
Sign up to set email alerts
|

Augmented cholesterol absorption and sarcolemmal sterol enrichment slow small intestinal transit in mice, contributing to cholesterol cholelithogenesis

Abstract: Key points• Peristaltic function of the small intestine is compromised in cholelithogenic humans and in animal models of cholesterol gallstones.• In a mouse gallstone model fed a cholesterol-and cholic acid-enriched diet, we show that slowing of small intestinal transit is due to absorption of excess cholesterol molecules from the upper small intestine followed by their incorporation into sarcolemmal membranes of smooth muscle cells.• Blocking cholesterol absorption with ezetimibe (Zetia), an inhibitor of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 74 publications
1
15
0
Order By: Relevance
“…We show here that feeding the lithogenic diet has the same effect due to impairment of CCK secretion. Our findings are also consistent with the previous demonstration that feeding mice a lithogenic diet slows small intestinal motility due to excessive incorporation of absorbed cholesterol into intestinal smooth muscle sarcolemmal membranes [34]. The authors inferred that this excessive cholesterol enrichment of intestinal smooth muscle cells produced hypomotility by uncoupling CCK signal transduction, a physiological mechanism of stimulated small intestinal propulsion.…”
Section: Psti-isupporting
confidence: 93%
“…We show here that feeding the lithogenic diet has the same effect due to impairment of CCK secretion. Our findings are also consistent with the previous demonstration that feeding mice a lithogenic diet slows small intestinal motility due to excessive incorporation of absorbed cholesterol into intestinal smooth muscle sarcolemmal membranes [34]. The authors inferred that this excessive cholesterol enrichment of intestinal smooth muscle cells produced hypomotility by uncoupling CCK signal transduction, a physiological mechanism of stimulated small intestinal propulsion.…”
Section: Psti-isupporting
confidence: 93%
“…This engenders hyperabsorption of Ch from the upper small intestine generation of a secondary bile acid deoxycholic acid in the distal small intestine. 29 Inflammatory changes in the lamina propria and muscle hypertrophy occur in these mice 4 weeks after they are fed lithogenic diets but before gallstones are formed. 30 These changes do not occur when mice are pretreated with maximum doses of ezetimibe that blocks completely the intestinal absorption of Ch.…”
Section: Role Of Lithogenic Bile With Excess Cholesterol In the Pathomentioning
confidence: 97%
“…Lithogenic diets fed to C57L mice impair the contractility of muscle cell layers of the small bowel resulting in slower intestinal transit. This engenders hyperabsorption of Ch from the upper small intestine generation of a secondary bile acid deoxycholic acid in the distal small intestine . Inflammatory changes in the lamina propria and muscle hypertrophy occur in these mice 4 weeks after they are fed lithogenic diets but before gallstones are formed .…”
Section: Role Of Lithogenic Bile With Excess Cholesterol In the Pathomentioning
confidence: 99%
“…The authors observed a chemoprotective action of FA supplementation in this gastric cancer model because of the ability of FA to prevent global loss of methylation and suppress inflammation. In addition, Xie et al [40] demonstrated that the lithogenic diet, but not H. hepaticus infection, significantly contributes to slowing of small intestinal transit in C57L/J mice.…”
Section: Pathogenesis and Immune Responsementioning
confidence: 99%